Intracerebral Hemorrhage - Chaudhary, Vikas (IntechOpen, 2014)
Intracerebral hemorrhage is an important clinical entity encountered in practice. Common causes of intracerebral hemorrhage include hypertension, amyloid angiopathy, trauma, coagulopathy, arteriovenous malformation and underlying tumor. Advances in imaging techniques have helped in better understanding of pathogenesis and the mechanisms of recovery of intracerebral hemorrhage, thereby resulting in marked improvement in its management. I hope that this book on intracerebral hemorrhage will be a useful learning tool for students and clinicians in the field of neuroscience.